Characteristics and Situation of Fire in China From 1999 to 2019: A Statistical Investigation - Xiong, Yachao; Zhang, Changli; Qi, Hui; Liu, Xizhao (Frontiers in Environmental Science, 2022)
Fire is one of the disasters that frequently threaten public safety and social development, especially in developing countries such as China. The occurrence and spread of fire have distinctive characteristics. The analysis of fire causes and the summary of the unique patterns of fire with socioeconomic development and time can provide guidance and services for fire prevention. Therefore, based on the official data of China from 1999 to 2019, the current situation of fires in China is described in terms of four indicators, including the number of fires, the number of deaths, the number of injuries, and direct losses. In addition, the current situation, temporal volatility, and causes of the more severe fires in China were analyzed. The entropy weight-TOPSIS model was used to assess the fire patterns in China in the last two decades. The spatial correlation of fires in each province of China was analyzed by the Moran’s I index and LISA index. The results show that the overall fire situation in China has improved in the last two decades. Still, the spatial aggregation of fires is becoming more and more apparent, and human factors are the leading cause of fires in China. The study can provide a theoretical and decision-making basis for fire situation prognosis, fire prevention, and effective spatial allocation of fire prevention resources in China and other countries.